(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The study aims to indicate the role of strategic financial accounting in the service investors to take appropriate decisions in the future, Through what is provided by the strategic accounting, the future of information and data that enable the investor to make future investment decisions appropriate، If no longer traditional financial accounting putting meet all existing and prospective investors Requirements، That reliance on historical data and information already signed and neglected aspect of future, From this point it was to highlight the role of strategic financial accounting to contribute in this area.